Design of a Web-Based Goods Inventory Information System for an Office Stationery Store - Pathak, Vijey North Sandep; Robbi Rahim; Rahmania; Kamaruddin; Erwin Gatot Amiruddin (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2024)
Hasco Stationery Store, located on Jalan Perintis Kemerdekaan Km 09, is a business specializing in printing and office stationery sales. Effective management of stock availability, purchasing, and sales processes is crucial to meeting customer needs. Prior to implementing an integrated information system, inventory management at the store was performed manually by employees, who relied on estimates and experience to record stock, check inventory, and place purchase orders. This manual approach proved inefficient and prone to errors, including inaccurate stock calculations, recording mistakes, and data loss. To address these challenges, this study employed the waterfall development method to design and implement a web-based inventory information system aimed at enhancing the efficiency and accuracy of inventory management processes. Data were collected through interviews with the store owner, direct observations, and analysis of relevant documents, supplemented by a literature review on stock management principles and information system development. The resulting system simplifies stock management, reduces errors, and improves overall operational efficiency, providing a robust solution for inventory management at the Hasco Stationery Store.